Original paperNeopterin and circulating adhesion molecules as prognostic markers in childhood asthma - Hatzistilianou, Maria; Haidopoulou, Katerina; Eboriadou, Maria; Papastavrou, Theodouli; Magnesali, Christina; Pappa, Stella (Archives of Medical Science, 2007)
Introduction: The purpose of this study was to determine the serum levels of neopterin and circulating adhesion molecules sICAM-1, sE-selectin and sL-selectin in children with stable asthma in order to investigate their possible role in the pathogenesis of chronic inflammation in asthma. We also compared atopic and non-atopic asthmatic children in order to detect differences between groups, possibly reflecting different mechanisms involved in chronic inflammation of the airways. Material and methods: The study included three groups of children: A, B and C. Group A consisted of 30 children with atopic asthma, group B of 30 children with non-atopic asthma and group C (control group) of 20 healthy children. All asthmatic children had been diagnosed with mild to moderate persistent asthma according to the International Paediatric Asthma Consensus Group Reports and were studied during a stable phase of their disease. The asthmatic children were divided into atopic and non-atopic, as judged by the presence of a positive or negative skin prick test or a positive specific IgE test. Results: There were no differences in serum sICAM-1, sE-selectin or sL-selectin levels between groups A, B and C. Atopic asthmatic children had significantly higher levels of neopterin compared to the non-atopic asthmatics or healthy children (p<0.001). Conclusions: Our data support the hypothesis that neopterin is produced and secreted by activated macrophages, the latter playing a role in chronic asthmatic inflammation. This may allow a better understanding of the clinical implications and more insight into the inflammatory processes of bronchial asthma.